Comparative analysis of household waste composition in Kigali and Lome with a view to sustainable management - inès, Ekpawou elzame; coffi, Aholou; placide, Cledjo; patouki, Sing-non bourdannet; Mathieu, Jean pierre (Edelweiss Applied Science and Technology, 2025)
This article presents a comparative analysis of the composition of household waste in two African capitals: Lome (Togo) and Kigali (Rwanda). Based on data from characterization surveys and secondary studies, it highlights the dominant types of waste in each city and the resulting dynamics. In Lome, plastic (39%) and glass (28%) waste are the most prevalent, reflecting the widespread use of single-use packaging and the common consumption of bottled beverages. In Kigali, waste is dominated by plastics (32%) and tin cans (29%), reflecting a diet that is more focused on processed and imported products. The low proportion of organic waste in both contexts raises questions about domestic recovery or disposal practices. These results illustrate the impact of lifestyles, levels of urbanization, public policies, and consumption habits on the types of urban waste. The study highlights the need to adapt waste management policies to local realities in order to promote a circular and sustainable economy.